PERFORMANCE EVALUATION OF THE VEGETABLE TRADING CENTER IN LANTAPAN, BUKIDNON, PHILIPPINES - Karen Debbie Jabenar Cosrojas (Socio-Economics/Agribusiness Department, 2021)
This paper evaluated the performance of the project: “Farmer Cluster-Managed Bagsakan (trading center) Model in Lantapan, Bukidnon”. It used the CIPP and OECD-DAC evaluation frameworks to make sense of the data. The said project envisioned to operate a farmer-cluster managed bagsakan center. The bagsakan was operationalized and result shows that farmers derived higher profit when they brought their products in the center compared to marketing it to major cities. Other outputs of the project are the trainings conducted but these did not reflect significant contribution to the bagsakan operation. In terms of the relevance of the project, its objective is found valid because it answers to the needs and problems confronting the vegetable farmers. Effectiveness assessment tells that to a little extent the project’s objective was attained given the bagsakan’s operationalization. Sustainability measurement of the project was not realized since the operation only lasted for one year.